SILENT SUFFERING: POSTGRADUATE STUDENTS’ COPING MECHANISMS IN THE FACE OF SUPERVISORY CHALLENGES – A QUALITATIVE CROSS-SECTIONAL STUDY DESIGN. - Mbanjwa, Sibonelo Thanda (Student’s Journal of Health Research Africa, 2025)
Background This study investigates the coping mechanisms employed by master ’s-level postgraduate students in response to supervision challenges within a South African university. Methods A qualitative cross-sectional single case study was conducted at a South African public university within the Faculty of Natural Sciences. Fifteen master’s students (9 females, 6 males) aged 24–36, from disciplines such as Environmental Science, Chemistry, and Microbiology, were purposively selected. All participants had engaged in research-based supervision for at least six months. Data were collected via in-depth semi-structured interviews and analysed thematically using Braun and Clarke’s approach. Results Twelve out of 15 participants reported psychological stress due to supervision-related issues. Common challenges included supervisor unavailability (13 students), delayed or infrequent feedback (11), and lack of academic guidance (9). Adaptive coping strategies included peer support (10), informal academic support networks (8), and proactive clarification with supervisors (5). Conversely, maladaptive responses included emotional withdrawal (6), avoidance of meetings (4), and procrastination on research tasks (5). Notably, 13 students were unaware of institutional grievance procedures or academic support services. Conclusion Master’s students frequently endure supervision challenges in silence, lacking knowledge of institutional support mechanisms. While some adopt positive coping strategies, others disengage emotionally or academically, compromising research progress and well-being. These findings highlight the need for structural interventions to support postgraduate mental health and academic resilience. Recommendations Universities should implement mandatory orientation for students and supervisors, establish safe reporting channels, train supervisors in communication and mentorship, and promote peer mentoring and mental health awareness initiatives.